Structural Transformation in Developed and Developing Countries - El-hadj Bah (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
Differences in key features of the development process across rich and poor countries can provide clues to the sources of the large variation of cross-country income. Kuznets included structural transformation as one of six stylized facts of economic development, nding that developed countries all followed the same process. In this paper, I compare structural transformation processes in developed and developing countries. I nd that developing countries follow distinct structural transformation paths that deviate from that followed by developed countries. A puzzling nding is the presence of substantial sectoral changes during times of economic stagnation or decline.
Keywords: O10; O11; O14; O57; 330; Africa; Asia; Latin America; Structural Transformation; Economic Development; Structural Change